Characteristics of leachate upon hydrothermal treatment processing: case study of Ampang district municipal solid waste leachate - Hadi, Purwanto; Khamis, Siti Salwa; Mohd. Salleh, Hamzah; Rozhan, Alya Naili; Abd Rahman, Mohamed; Othman, Rashidi (IIUM Press, 2022)
Municipal solid waste (MSW) leachate is a hazardous liquid produced from decomposition of solid waste with high amount of organic matter and ammonia-nitrogen with obnoxious smell. This study aimed to investigate the behavior of MSW leachate when subjected to hydrothermal treatment using an autoclave set up at below water critical points (temperatures of 100 °C, 150 °C, and 200 °C at 0.1 MPa, 0.4 MPa and 1.6 MPa, respectively) with 15 min and 60 min holding time. Physicochemical characterization of the setup at 200 °C and 1.6 MPa at 60 min holding time indicates a feasible parameter when materials that caused the dark color and obnoxious smell were almost completely removed. Over 99% of chemical oxygen demand and ammonia nitrogen was eliminated when treated with hydrothermal treatment and yielded a condensed liquid product that complied with permissible limits set by the National Water Quality Standard Malaysia and the World Health Organization for wastewater discharges for irrigation purposes. Chromatographic analysis indicated that most of the organic compounds present in the raw leachate was removed. This processing is believed to be an environmentally friendly method that can treat MSW leachate rapidly, and it has the potential to be used as an effective alternative to existing leachate treatment technologies.